COVID-19 insights and linguistic methods - Tan, Kim Hua; Peter Woods,; Hazita Azman,; Imran Ho Abdullah,; Ruzy Suliza Hashim,; Hajar Abdul Rahim,; Mohd Muzhafar Idrus,; Nur Ehsan Mohd Said,; Lew, Robert; Kosem, Iztok (Penerbit Universiti Kebangsaan Malaysia, 2020)
The emergence of COVID-19 affects the world population in many ways, resulting in its own specialised discourse. In addition to providing a source of data for analysis, this discourse has also led to a rethinking of multifarious research methods. This section presents a series of articles by scholars from different parts of the world with macro- and micro-linguistic perspectives, ranging from corpus-based analysis to content analysis studies. At the macro level, these scholars explored ways through which government bodies communicate with the public. Official announcements, parliamentary proceedings and COVID-19-related corpora are examined and a comparative textual analysis between the Malaysian and British governments is provided. At the micro level, the scholars analysed selected corpora with lexical, semantic, and discourse foci and personal posts of short narratives and photos to encapsulate meanings from human life and experience. The main takeaway from these studies is the application of a wide range of methods for different focus and perspectives that may be customised to the researcher’s unique context.